Implementasi Hybrid Metode Teorema Bayes dan Certainty Factor Dalam Mendiagnosa Penyakit Motile Aeromonas Septicaemia - Badrul Anwar; Muhammad Syahril; Rini Kustini (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
During the COVID-19 pandemic, many people lost their jobs, resulting in a decline in the level of the economy in Indonesia, coupled with restrictions on outdoor activities, thus making many people turn to work as home-based entrepreneurs, one of which is in the fishery sector, namely catfish, which is a home-based business. easy but with a promising income, thus creating new catfish farmers who lack knowledge, resulting in many new entrepreneurs failing to harvest, especially in handling diseases that often attack catfish, namely MAS (Motile Aeromonas Septicamea) which results in losses for farmers. From this problem, to make it easier for farmers to detect disease in sangkuriang catfish, an expert system application was designed and built using the Hybrid Bayes Theorem and Certainty Factor method to diagnose Mas disease (Motile Aeromonas Septicamea) and provide solutions for handling sangkuriang catfish. The result of this study is to facilitate catfish farmers in diagnosing Mas (Motile Aeromonas Septicamea) disease that attacks sangkuriang catfish